ACHIEVING SUSTAINABLE DEVELOPMENT GOALS 4 BY CREATING AN INCLUSIVE SCHOOL ENVIRONMENT THROUGH LITERACY PROGRAM INTEGRATED WITH THE ANTI-BULLYING PROGRAM - Zidniyati, Zidniyati; Faizah, Kurniyatul; Anggraeni, Lia (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
This study aimed to create a literate and inclusive school environment by providing literacy and anti-bullying training to elementary school teachers and principals. The research was conducted in 20 primary schools in Banyuwangi Regency, Indonesia over three years from 2021 to 2023. In the first year, the focus was on a balanced literacy program that followed key stages: 1) developing reading and writing habits, 2) searching, browsing, processing, and understanding information, 3) analyzing, responding, and using written texts, and 4) developing understanding and potential to participate in the social environment. The second year focused on an anti-bullying program that targeted indicators like setting consistent rules, creating inclusive study groups, and identifying potential behavior problems. By the third year, 75% of teachers were able to create literacy-rich and inclusive classroom environments, apply consistent rules, and conduct ongoing socialization with other teachers. The results showed improvements in teachers' abilities to implement balanced literacy activities, use reading comprehension methods, create student-authored books, and apply anti-bullying strategies. The study concludes that the integrated literacy and anti-bullying program was successful in preparing students with strong literacy skills while also creating a safe and inclusive learning environment. Overall, this research demonstrates how a holistic approach targeting both literacy development and anti-bullying measures can lead to positive outcomes for elementary school students.